2014
DOI: 10.1021/jp410895c
|View full text |Cite
|
Sign up to set email alerts
|

CO Adsorption on Clean and Oxidized Pd(111)

Abstract: The adsorption of CO on clean and oxidized Pd(111) surfaces has been investigated using a combination of high-resolution core level spectroscopy (HRCLS), reflection absorption infrared spectroscopy (RAIRS), and density functional theory (DFT) calculations. The HRCLS and RAIRS measurements reveal that CO adsorbs on Pd(111), Pd 5 O 4 and PdO(101) at 100 ± 10 K and that the CO coverage decreases with increasing oxidation state of Pd for the same CO exposures of 10 Langmuirs. Based on the DFT calculations, the CO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
96
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(120 citation statements)
references
References 64 publications
23
96
1
Order By: Relevance
“…On the other hand, DFT model predictions (Zhang and Hu, 2001), propose a value of 1.6 eV (1 eV = 23.06 kcal/mol) for adsorption of CO on pre-adsorbed O on Pd (111). Similar energy predictions were also obtained from the DFT studies by Martin et al (2014) proposing a range of values from 1.82 eV-1.75 eV for CO adsorption on different adsorption sites on clean Pd (111).The equivalent range of chemisorption energy for CO adsorption has also been reported (Eichler, 2002;Zorn et al, 2011).This chemisorption energy of 34 kcal/mol is in good agreement with the ϭϱ experimental results (Engel and Ertl, 1979;Chou and Vannice, 1987a) and UHV studies (Szanyi et al, 1993;Stara and Matolin, 1994) on clean Pd (111). However, calorimetric studies (Conrad et al, 1974;Peter et al, 2013a) suggest coverage dependent activation energies for CO desorption on Pd (111). Conrad et al (1974) observed a constant value of CO desorption energy till coverage of 0.33 and then decreasing to 20 kcal/mol at higher coverages.…”
Section: Adsorption-desorption Of Cosupporting
confidence: 81%
“…On the other hand, DFT model predictions (Zhang and Hu, 2001), propose a value of 1.6 eV (1 eV = 23.06 kcal/mol) for adsorption of CO on pre-adsorbed O on Pd (111). Similar energy predictions were also obtained from the DFT studies by Martin et al (2014) proposing a range of values from 1.82 eV-1.75 eV for CO adsorption on different adsorption sites on clean Pd (111).The equivalent range of chemisorption energy for CO adsorption has also been reported (Eichler, 2002;Zorn et al, 2011).This chemisorption energy of 34 kcal/mol is in good agreement with the ϭϱ experimental results (Engel and Ertl, 1979;Chou and Vannice, 1987a) and UHV studies (Szanyi et al, 1993;Stara and Matolin, 1994) on clean Pd (111). However, calorimetric studies (Conrad et al, 1974;Peter et al, 2013a) suggest coverage dependent activation energies for CO desorption on Pd (111). Conrad et al (1974) observed a constant value of CO desorption energy till coverage of 0.33 and then decreasing to 20 kcal/mol at higher coverages.…”
Section: Adsorption-desorption Of Cosupporting
confidence: 81%
“…[35][36][37][38] Here, we present experimental and computational results for CO adsorption on PdO(101). We will show that inclusion of Fock exchange enhances the agreement between the calculated and measured CLS.…”
Section: Resultsmentioning
confidence: 99%
“…This CLS is clearly underestimated in PBE where it is calculated to be ∼1 eV. 35,44,45 Here, we investigate the influence of Fock exchange on the Pd 3d CLS between bulk palladium metal and bulk palladium oxide. As inclusion of both types of atoms in the same computational unit cell is advantageous to obtain accurate CLS, the calculations have been performed with a slab model consisting of commensurable Pd and PdO surfaces.…”
Section: B the Pd 3d Shift Upon Bulk Oxidation Of Pdmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, for Pd(111) we found the preference of fcc site with E ads (CO) amounting to À1.52 eV, in excellent agreement with the experimental data (À1.47 to À1.53 eV [49]). Also, the preference of highly coordinated sites on Pd(111) was observed experimentally [50,51]. Theoretical reports for CO adsorption energy fall in the range from about À1.1 to À1.9 eV [51].…”
Section: Chemisorption Propertiesmentioning
confidence: 81%